2019
DOI: 10.1038/s41598-019-52840-z
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of LINEs and species-specific DNA repeats drives genome expansion in Asian Gypsy Moths

Abstract: Two subspecies of Asian gypsy moth (AGM), Lymantria dispar asiatica and L. dispar japonica, pose a serious alien invasive threat to North American forests. Despite decades of research on the ecology and biology of this pest, limited AGM-specific genomic resources are currently available. Here, we report on the genome sequences and functional content of these AGM subspecies. The genomes of L.d. asiatica and L.d. japonica are the largest lepidopteran genomes sequenced to date, totaling 921 and 999 megabases, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…By contrast, TE represent less than 1% of the genomes of the Antarctic midge ( Belgica antarctica , Diptera, 83.9 Mb) ( Kelley et al., 2014 ) and the body louse ( Pediculus humanus humanus , Phthiraptera, 108 Mb) ( Kirkness et al., 2010 ). Some studies have reported that the specific accumulation of LINE retrotransposons and DNA transposons leads to GS variation among wood-white butterfly species (genus Leptidea ) ( Talla et al., 2017 ) and Asian gypsy moths (genus Lymantria ) ( Hebert et al., 2019 ). In addition, the massive horizontal transfer of some TEs, such as the Gypsy, Bel-Pao, and Copia LTR superfamilies, significantly influences GS in mosquitoes ( Melo and Wallau 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, TE represent less than 1% of the genomes of the Antarctic midge ( Belgica antarctica , Diptera, 83.9 Mb) ( Kelley et al., 2014 ) and the body louse ( Pediculus humanus humanus , Phthiraptera, 108 Mb) ( Kirkness et al., 2010 ). Some studies have reported that the specific accumulation of LINE retrotransposons and DNA transposons leads to GS variation among wood-white butterfly species (genus Leptidea ) ( Talla et al., 2017 ) and Asian gypsy moths (genus Lymantria ) ( Hebert et al., 2019 ). In addition, the massive horizontal transfer of some TEs, such as the Gypsy, Bel-Pao, and Copia LTR superfamilies, significantly influences GS in mosquitoes ( Melo and Wallau 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the proportion of LINE elements identified in the S. littoralis genome was the highest reported so far in arthropods 78 , accounting for 52.18% of all repetitive elements. In two subspecies of the Asian gypsy moth Lymantria dispar, the accumulation of this particular class of transposable elements was found to be responsible for their large genome size 79 , a phenomenon also observed in other insect species 75 . The accumulation of the same elements in the S. littoralis genome could explain its larger size compared to its Spodoptera counterparts (470Mb vs ~400Mb for S. frugiperda, 438Mb for S. litura, 408-448Mb for S. exigua).…”
Section: Annotation Of Transposable Elements Enrichment Analysis and Selection Pressurementioning
confidence: 67%
“…Remarkably, the proportion of LINE elements identified in the S. littoralis genome was the highest reported so far in arthropods ( Petersen et al 2019 ), accounting for 52.18% of all repetitive elements. In 2 subspecies of the Asian gypsy moth Lymantria dispar , the accumulation of this particular class of TEs was found to be responsible for their large genome size ( Hebert et al 2019 ), a phenomenon also observed in other insect species ( Maumus et al 2015 ). The accumulation of the same elements in the S. littoralis genome could explain its larger size compared with its Spodoptera counterparts (465 Mb vs ∼400Mb for S. frugiperda , 438 Mb for S. litura , 408–448 Mb for S. exigua ).…”
Section: Resultsmentioning
confidence: 85%